Mild and General Protocol for Selective Deacetylation of Acetyl/Benzoyl-Protected Carbohydrates; Journal of Organic Chemistry; Vol. 89, iss.14 - Abramov A. A. Aleksandr Aleksandrovich; Zinin A. I. Aleksandr Ivanovich; Kolotyrkina N. G. Natalya; Kononov L. O.; Shatskiy A. Andrey; Karkas M. D. Markus; Stepanova E. V. Elena Vladimirovna (2025, 2025)
Title screen